2017
DOI: 10.4239/wjd.v8.i9.429
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of diabetes at diagnosis among children and adolescents at an endocrine clinic in Ghana

Abstract: AIMTo determine the clinical features of diabetes in children and adolescents in Ghana.METHODSRetrospective review of clinical features of all children and adolescents with new-onset diabetes seen at the paediatric endocrinology clinic of Komfo Anokye Teaching Hospital in Kumasi, from February 2012 to Auguest 2016.RESULTSOne hundred and six subjects presented with diabetes. Ninety (84.9%) were diagnosed by clinical features and family history as type 1, and 16 (15.1%) type 2. For type 1 subjects, age range at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 27 publications
5
21
0
Order By: Relevance
“…Mortality rates fall sharply as care (including management of diabetic ketoacidosis) begins to improve, and thus prevalence increases …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mortality rates fall sharply as care (including management of diabetic ketoacidosis) begins to improve, and thus prevalence increases …”
Section: Introductionmentioning
confidence: 99%
“…35,36 Although analog insulin is almost universally preferred over human insulin by health care professionals and people with type 1 in well-resourced countries, it is important to note that, despite many studies, improvements in HbA1c levels have not been showed. 32,35,336 It is accepted that analog insulin helps to reduce rates of nocturnal hypoglycemia in well-resourced settings. 32,35,37 Therefore, when funds are limited, it is much more important to have more frequent SMBG rather than analog insulin.…”
Section: Introductionmentioning
confidence: 99%
“…The national EML for Ghana includes short-acting, intermediate-acting and premixed human insulins as well as analogue insulins and glucagon [16]. However, only short- and intermediate-acting human insulins are (irregularly) available through the NHIS [13]. The cost of a vial of insulin (1,000 units) varies from 0 USD (insured patient when insulin is available at the hospital pharmacy) to 7 USD (insured patient who buys the insulin from a nonhospital pharmacy) and 15 USD (nonsubsidized price).…”
Section: Resultsmentioning
confidence: 99%
“…Mortality and morbidity is likely underreported because clinical features of pediatric endocrine diseases and of diabetes may mimic infections and other common medical conditions, causing misdiagnosis [39, 40]. In addition, a complete neonatal examination is not routinely performed in many settings, preventing the diagnosis of congenital conditions such as disorders of sexual development [13, 41]. It is expected that the increase in capacity in pediatric endocrinology will lead to a better understanding of the prevalence and characteristics of pediatric endocrine diseases and diabetes which, in turn, will drive advocacy for essential medicines that are presently not available to the patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation